Reducing Emissions from Deforestation and Forest Degradation (REDD) in Nepal: Exploring the Possibilities - Dhital, Narayan (Journal of Forest and Livelihood, 2009)
This article argues that Nepal can benefit from the REDD mechanism by proactively acting to curb the rate of deforestation and forest degradation. Successful participation can bring biodiversity, ecological and economic benefits to the community as well as the country. Nevertheless, technical complexities in assessing the market, elite domination in contract negotiation and risk of ignoring the voices of forest?dwelling communities pose serious threats to the success of the plan. Key words: REDD, community?managed forests, carbon sequestration, deforestation, climate change Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.56-61